Dlaczego nie ma taśm z powstania wielkopolskiego? - Hendrykowski , Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article is a monographic study of the moving picture of Wielkopolska Uprising 1918–1919. The author indicates the reasons of a lack of film archives concerning Posnanian War.